NEUROSCIENTIFIC EVIDENCE AND CARE LEAVING: A MULTIDISCIPLINARY CRITICAL COMMENTARY - Sundly, Amit; Keating, Meghan; Effiong, Andem; Saif, Abdullah Omar (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2023)
While neuroscientific literature suggests that some parts of the brain are not fully developed until the mid-20s, public discourse is skewed toward early child development (ECD) because of its supposed long-term economic benefits. Some researchers have gone so far as to say that society overinvests in remedial programs for disadvantaged adolescents. Such claims resist advocacy efforts for extended care for children in out-of-home care and discourage policy and legislative concerns regarding investing in early adulthood. In this commentary, we unpack the literature on brain development and critically discuss its selective use by legislators and policymakers for investments in ECD. Despite the availability of neuroscientific and economic evidence, it is not prominent in the discourse surrounding supportive interventions like extending care. Using Bourdieu’s theory of social reproduction, we discuss how preference is given to only the type of knowledge that preserves the social structures that work to ensure the multigenerational flow of capital among dominant groups. Also, social institutions act within the dimensions set by the social structure, constantly shaping and reshaping ways of facilitating capital preservation among the upper classes. We conclude that, in addition to moral argument, the current neuroscientific evidence may support investment in extended care programs.